2008
DOI: 10.1177/0883911508089932
|View full text |Cite
|
Sign up to set email alerts
|

Light-Cured Dimethacrylate-Based Resins and Their Composites: Comparative Study of Mechanical Strength, Water Sorption, and Ion Release

Abstract: This study explored how resin type affects selected physicochemical properties of complex methacrylate copolymers and their amorphous calcium phosphate (ACP)-filled and glass-filled composites. Two series of photo-polymerizable resin matrices were formulated employing 2,2-bis [p-(2'-hydroxy-3'-methacryloxypropoxy)phenyl]propane (Bis-GMA) or an ethoxylated bisphenol A dimethacrylate (EBPADMA) as the base monomer, Unfilled copolymers and composites filled with a mass fraction with 40 %, 35 % and 30 %, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
13
1
2
Order By: Relevance
“…Zirconia hybridized ACP (Zr-ACP) was prepared according to our previously published protocol [19, 20]. The amorphous state of the filler was verified by X-ray diffractometry (Rigaku DMAX 2000 X-ray diffractometer, Rigaku/USA Inc., Danvers, MA, USA) and Fourier-transform infrared spectroscopy (Nicolet Magna-IR FTIR 550 spectrophotometer, Nicolet Instrumentations Inc., Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconia hybridized ACP (Zr-ACP) was prepared according to our previously published protocol [19, 20]. The amorphous state of the filler was verified by X-ray diffractometry (Rigaku DMAX 2000 X-ray diffractometer, Rigaku/USA Inc., Danvers, MA, USA) and Fourier-transform infrared spectroscopy (Nicolet Magna-IR FTIR 550 spectrophotometer, Nicolet Instrumentations Inc., Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of ACP sealants, solution solubility of ACP [18] enabled the release of supersaturating levels of calcium and phosphate ions intralesionally and shifted the solution thermodynamic driving forces toward the formation of apatite. ACP can sustain these supersaturation conditions over extended periods of time [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, ACP composites trail behind conventional glass-based dental composites in terms of mechanical strength. 10 Many treatments, such as filler hybridization 13,14 or milling, [15][16][17] surface treatment of the filler, 9 and use of various methacrylic polymer matrices, [18][19][20][21] have been explored for optimizing the mechanical properties of the ACP-based dental composites for potential clinical applications. Notably, a comparison of wet and dry ACP composites showed that the biaxial flexure strength of the composites is strongly related to the uptake of water in these composites -more water, less strength, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…There is a very limited number of studies evaluating the effects of organic acids on the leaching of monomers [20], but there are several reports regarding the effects of organic acids on the mechanical and surface characteristics of composite resins [5, 21]. Asmussen has reported that the hardness of resin composite significantly decreased after 1 d of immersing in ethanol, acetic acid, propionic acid, and lactic acid [8].…”
Section: Discussionmentioning
confidence: 99%